Mechanisms of complement activation, C4d deposition, and their contribution to the pathogenesis of antibody mediated rejection - Murata, Kazunori (2009)
Complement split products have emerged as useful markers of antibody mediated rejection in solid organ transplants. One split product, C4d, is now widely accepted as a marker for antibody mediated rejection in renal and cardiac allografts. This review summarizes the rationale for the use of C4d as a marker of antibody mediated rejection, along with the clinical evidence supporting its use in the clinical diagnosis of antibody mediated rejection. Antibody-independent mechanisms by which C4d can be activated by the classical and lectin pathways of complement activation are also identified. Finally, mechanisms by which complement activation stimulates effector cells (neutrophils, monocytes, macrophages, platelets, and B and T lymphocytes) as well as target cells (endothelial cells) are discussed in relation to antibody mediated allograft rejection.